Association between childcare educators' practices and preschoolers' physical activity and dietary intake: a cross-sectional analysis. Issue 5 (30th May 2017) - Ward, Stéphanie; Blanger, Mathieu; Donovan, Denise; Vatanparast, Hassan; Muhajarine, Nazeem; Engler-Stringer, Rachel; Leis, Anne; Humbert, M Louise; Carrier, Natalie
Abstract : Introduction: Childcare educators may be role models for healthy eating and physical activity (PA) behaviours among young children. This study aimed to identify which childcare educators' practices are associated with preschoolers' dietary intake and PA levels. Methods: This cross-sectional analysis included 723 preschoolers from 50 randomly selected childcare centres in two Canadian provinces. All data were collected in the fall of 2013 and 2014 and analysed in the fall of 2015. PA was assessed using Actical accelerometers during childcare hours for 5 consecutive days. Children's dietary intake was measured at lunch on 2 consecutive days using weighed plate waste and digital photography. Childcare educators' nutrition practices (modelling, nutrition education, satiety recognition, verbal encouragement and not using food as rewards) and PA practices (informal and formal PA promotion) were assessed by direct observation over the course of 2 days, using the Nutrition and Physical Activity Self-Assessment for Child Care tool. Associations between educators' practices and preschoolers' PA and dietary intake were examined using multilevel linear regressions. Results: Overall, modelling of healthy eating was positively associated with children's intake of sugar (β=0.141, 95% CI 0.03 to 0.27), while calorie (β=−0.456, 95% CI −1.46 to –0.02) and fibre intake (β=−0.066, 95% CI −0.12 to –0.01) were negatively associated with providing nutrition education. Not using food as rewards was also negatively associated with fat intake (β=−0.144, 95% CI −0.52 to –0.002). None of the educators' PA practices were associated with children's participation in PA. Conclusions: Modelling healthy eating, providing nutrition education and not using food as rewards are associated with children's dietary intake at lunch in childcare centres, highlighting the role that educators play in shaping preschoolers' eating behaviours. Although PA practices were not associated with children's PA levels, there is a need to reduce sedentary time in childcare centres.